2011
DOI: 10.1111/j.1476-5381.2011.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol and salmeterol induce a similar degree of β2‐adrenoceptor tolerance in human small airways but via different mechanisms

Abstract: BACKGROUND AND PURPOSESteroids prevent and reverse salbutamol-induced b2-adrenoceptor tolerance in human small airways. This study examines the effects of the long-acting b2 agonists (LABAs) formoterol and salmeterol, and the ability of budesonide to prevent desensitization. EXPERIMENTAL APPROACHLong-acting b2 agonists in the presence and absence of budesonide were incubated with human precision-cut lung slices containing small airways. Tolerance was deduced from measurements of reduced bronchodilator response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 39 publications
(43 reference statements)
5
45
0
1
Order By: Relevance
“…In summary, our BRET findings strongly support the conclusion that short-term salmeterol desensitization via the GRK pathway is diminished by its reduced efficacy for arrestin binding. In support of this conclusion, the observation of a deficit in salmeterol-induced internalization via GRK/arrestin was also demonstrated in HAMC cells by immunolocalization of yellow fluorescent protein-tagged b2AR after salmeterol stimulation (Cooper et al, 2011), in mouse myoblast C2C12 cells using a galactosidase complementation assay (Carter and Hill, 2005), and in HEK 293 cells by arrestin translocation (van der Westhuizen et al, 2014) and fluorescence resonance energy transfer (Drake et al, 2008). Furthermore, it was also shown that knockdown of arrestin reduces functional desensitization (Deshpande et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In summary, our BRET findings strongly support the conclusion that short-term salmeterol desensitization via the GRK pathway is diminished by its reduced efficacy for arrestin binding. In support of this conclusion, the observation of a deficit in salmeterol-induced internalization via GRK/arrestin was also demonstrated in HAMC cells by immunolocalization of yellow fluorescent protein-tagged b2AR after salmeterol stimulation (Cooper et al, 2011), in mouse myoblast C2C12 cells using a galactosidase complementation assay (Carter and Hill, 2005), and in HEK 293 cells by arrestin translocation (van der Westhuizen et al, 2014) and fluorescence resonance energy transfer (Drake et al, 2008). Furthermore, it was also shown that knockdown of arrestin reduces functional desensitization (Deshpande et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
“…Our studies demonstrated that short-term treatment of the b2AR with salmeterol caused much reduced desensitization compared with strong agonists in membrane assays (Clark et al, 1996;January et al, 1998). On the basis of studies comparing the effects of equieffective concentrations of salmeterol and strong agonists on functional desensitization in human airway smooth muscle (HASM) cells by measure of either cAMP accumulation or bronchodilation and bronchoprotection, it was concluded that salmeterol was a strong agonist (Düringer et al, 2009;Cooper et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inhibiting GRK2/3 or blocking ␤-arrestin-2 can selectively enhance ␤ 2 AR signaling in human ASM (60). Here, corticosteroids, a mainstay of asthma therapy, can also help restore ␤-agonist sensitivity and prevent desensitization although such effects may be specific to particular ␤-agonist agents (47). With TAS2R, recent but limited data based on prevention of desensitization by dynamin but lack of effect of PKA or PKC antagonists (256) also suggest a role for GRK/␤-arrestins.…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…To determine if hAMs are the true C. burnetii target cell, we extended our studies to intact ex vivo human lung tissue to study initial interactions between C. burnetii and its human host. Lung tissue was sectioned into 750-m-thick slices termed precision-cut lung slices (PCLS) (17) and incubated in tissue culture plates. We visualized PCLS by bright-field microscopy ( Fig.…”
Section: Resultsmentioning
confidence: 99%